Enthusiasm for cancer screening in Great Britain: a general population survey - Waller, J (Br J Cancer, 2015)
BACKGROUND: With growing concerns about risk of harm from cancer screening, particularly from overdiagnosis, this study aimed to assess public attitudes to cancer screening in Great Britain. METHODS: We used a population-based survey to assess attitudes to cancer screening, screening history and demographic characteristics, in men and women aged 50–80 years. Data were collected using face-to-face computer-assisted interviews in 2012. RESULTS: In our sample of 2024, attitudes to cancer screening were overwhelmingly positive with almost 90% believing that screening is ‘almost always a good idea' and 49% saying they would be tested for cancer even if it was untreatable. Attitudes were particularly positive among those who had previously taken part in breast or colorectal screening. CONCLUSIONS: Our findings suggest that attitudes to cancer screening are very positive in Great Britain. Widespread enthusiasm for cancer screening may hamper attempts to encourage a greater appreciation of the limitations and potential harms of screening.